The role of village midwives in health services: A narrative review - Arinta, Pinta; Sudrajat, Hendra (STIKes Al-Ma'arif Baturaja, 2025)
Background: Maternal mortality in Indonesia remains relatively high, making the strengthening of maternal and child health services at the community level a national priority. Village midwives play a strategic role as the frontline providers in primary health care; however, the effectiveness of their role is influenced by multiple factors. Objective: This article aims to comprehensively examine the role of village midwives in health service delivery and the factors influencing their performance. Methods: This study employed a narrative review design. Articles were retrieved from PubMed, Scopus, Google Scholar, and national journal portals. Eligible publications were written in English or Indonesian between 1992 and 2024 and discussed the roles, competencies, performance, organizational support, leadership, and challenges of village midwives. Relevant studies were analyzed narratively and grouped according to thematic categories. Results: Four main themes were identified that influence the role of village midwives: (1) maternal and child health service roles; (2) competence and performance; (3) organizational support and leadership; and (4) structural challenges in remote areas. Village midwives have been shown to enhance access to maternal and neonatal health services; however, they continue to face barriers such as low incentives, inadequate facilities, limited supervision, and a lack of continuous training. Organizational support, supportive leadership, and educational investment were found to improve midwives’ performance and retention. Conclusion: Strengthening the role of village midwives requires a comprehensive approach involving continuous education, needs-based training, mentoring, organizational support, and affirmative policies, particularly for remote areas. These efforts are expected to significantly contribute to reducing maternal and neonatal mortality rates and strengthening primary health care services.